Pengaruh Kualitas Pelayanan Dan Disiplin Kerja Pegawai Terhadap Kepuasan Pasien ICU - Wawat Hermawati; Mahfud; Tumingsih (Journal Of Resource Management, Economics And Business, 2023)
Purpose: Examining the quality of service and work discipline on ICU patient satisfaction at Gunung Jati Hospital, Cirebon City and the extent to which service quality and work discipline influence jointly on patient satisfaction at Gunung Jati Hospital, Cirebon City. Research Methodology: The population in this study was all ICU patients at Gunung Jati Hospital, Cirebon City, totaling 398 people with a sample of 100 people using the Slovin formula. The data collection method uses a questionnaire. The data analysis techniques used in this research are correlation and multiple linear regression. Results: The research results show that service quality and work discipline have a significant effect on ICU patient satisfaction at Gunung Jati Regional Hospital, Cirebon City. The correlation coefficient result is 0.603. So it can be concluded that there is a positive influence between service quality and work discipline on ICU patient satisfaction at Gunung Jati Hospital, Cirebon City. Limitations: One limitation of this study is the sample size. The research was conducted with a sample of 100 ICU patients at Gunung Jati Hospital in Cirebon City. While efforts were made to ensure the representativeness of the sample, a larger sample size would have provided more robust results and increased generalizability. Additionally, the study focused specifically on ICU patient satisfaction at one hospital, which may limit the generalizability of the findings to other healthcare settings. Another limitation is the use of a questionnaire as the primary data collection method. Contribution: This study contributes to the understanding of the factors influencing ICU patient satisfaction in the context of Gunung Jati Hospital in Cirebon City. By examining the relationship between service quality, work discipline, and patient satisfaction, the study provides insights into the importance of these factors in healthcare settings. The findings can be beneficial for hospital administrators, healthcare professionals, and policymakers in improving service quality and promoting work discipline to enhance patient satisfaction in the ICU.